Memories of the midnight - Sheldon, Sidney (New York : Morrowand Company, 1990)
A beautiful American widow flees to a remote convent in Greece after an attempt on her life and becomes involved with a ruthless tycoon.
Keywords: Douglas, Catherine (Fictitious character) -- Fiction; Revenge -- Fiction; Suspense fiction -- Fiction